2013
DOI: 10.1109/tasl.2013.2239290
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Least Squares Methods for Joint DOA and Pitch Estimation

Abstract: In this paper, we consider the problem of joint direction-of-arrival (DOA) and fundamental frequency estimation. Joint estimation enables robust estimation of these parameters in multi-source scenarios where separate estimators may fail. First, we derive the exact and asymptotic Cramér-Rao bounds for the joint estimation problem. Then, we propose a nonlinear least squares (NLS) and an approximate NLS (aNLS) estimator for joint DOA and fundamental frequency estimation. The proposed estimators are maximum likeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 39 publications
1
61
0
Order By: Relevance
“…Moreover, a synthetic, multichannel periodic signal was used in every simulation with harmonics with unit amplitudes, and, in each simulation, the pitch and DOA were sampled from Hz Hz and , respectively, where denotes the continuous uniform distribution in the interval . The methods evaluated in these experiments are the optimal, white noise, and approximate filterbank ('bo', 'bw', and 'ba') and single filter ('so', 'sw', and 'sa') methods, the multichannel pitch estimator ('am') in [29], the steered response power method with phase transform ('sp') [30], and the exact and asymptotic nonlinear least squares (NLS) methods ('n' and 'an') in [10]. First, the performance of the proposed methods was evaluated for different 's in scenarios with 1) and an SNR of 30 dB, 2) and an SNR of 20 dB, and 3) and an SNR of 30 dB.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, a synthetic, multichannel periodic signal was used in every simulation with harmonics with unit amplitudes, and, in each simulation, the pitch and DOA were sampled from Hz Hz and , respectively, where denotes the continuous uniform distribution in the interval . The methods evaluated in these experiments are the optimal, white noise, and approximate filterbank ('bo', 'bw', and 'ba') and single filter ('so', 'sw', and 'sa') methods, the multichannel pitch estimator ('am') in [29], the steered response power method with phase transform ('sp') [30], and the exact and asymptotic nonlinear least squares (NLS) methods ('n' and 'an') in [10]. First, the performance of the proposed methods was evaluated for different 's in scenarios with 1) and an SNR of 30 dB, 2) and an SNR of 20 dB, and 3) and an SNR of 30 dB.…”
Section: Resultsmentioning
confidence: 99%
“…Another benefit is a potentially higher estimation accuracy. In [10], it was shown that the asymptotic Cramér-Rao bounds (CRBs) for the DOA and pitch are given by (13) (14) for the scenario described by (11) when is white noise and for , with PSNR denoting the pseudo signal-tonoise ratio. The PSNR is defined as (15) and is the variance of the noise.…”
Section: A Motivation For Joint Estimationmentioning
confidence: 99%
See 3 more Smart Citations